A vibration-based approach for damage identification and monitoring of prefabricated beam bridges. (September 2022) - Han, Fei; Dan, Danhui; Xu, Zhaoyuan; Deng, Zichen
As one of the most sophisticated structural types in rapid industrialized bridge construction technology, the fabricated beam bridge has been widely used in road network system for a long time. The prominent disease of this type of structure is the degradation of the lateral cooperative capability, that is, the deterioration of the hinge joint stiffness. This paper proposes a monitoring and evaluation method for the lateral connection stiffness based on the multiple-beams theory, which has the concise physical meanings and can be easily implemented. On this basis, a new damage identification method and index extracted from the mode shape information of the system is proposed in this paper. To verify the effectiveness of the proposed indicator ARCR, Shanghai Tongji Road viaduct is taken as the engineering background. Results shows that the theoretical analysis results are consistent with physical truth, the proposed indicator can reasonably reflect the degradation degree of the joint and locate the damaged joint.